2019
DOI: 10.1002/jpen.1696
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Mass Index Predicts Postoperative Complications in Intestinal Surgery for Crohn's Disease

Abstract: Background: The aim of this study was to evaluate the role of the skeletal muscle mass index (SMI) for major postoperative morbidity in patients with Crohn's disease (CD) and intestinal surgery at a tertiary referral center. Methods: A retrospective analysis of the prospectively maintained database for surgical patients with CD at our institution was performed. The cases of all patients operated on between December 2009 and December 2017 with sectional imaging prior to surgery were eligible for this study. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…It was found that IBD patients with sarcopenia had a higher probability of requiring surgery and significantly higher rates of major complications [ 9 ]. There are a number of studies that support these findings in terms of sarcopenia as a predictor of surgical intervention and reduced operation-free survival [ 20 , 24 , 128 , 129 ]. Indeed, there is an increase in post-surgical infections in those with sarcopenia, specifically surgical-site infections after restorative proctocolectomy for UC [ 130 ] and abscesses following intestinal surgery in CD [ 131 ].…”
Section: The Management Of Sarcopeniamentioning
confidence: 96%
“…It was found that IBD patients with sarcopenia had a higher probability of requiring surgery and significantly higher rates of major complications [ 9 ]. There are a number of studies that support these findings in terms of sarcopenia as a predictor of surgical intervention and reduced operation-free survival [ 20 , 24 , 128 , 129 ]. Indeed, there is an increase in post-surgical infections in those with sarcopenia, specifically surgical-site infections after restorative proctocolectomy for UC [ 130 ] and abscesses following intestinal surgery in CD [ 131 ].…”
Section: The Management Of Sarcopeniamentioning
confidence: 96%
“…Recent evidence suggests that psoas muscle cross sectional area is a practical surrogate measure of sarcopenia that can be readily and reliably measured by clinicians using standard image viewing software [ 21 ], as confirmed by our findings. A recent study [ 39 ], identified CT and MRI measurement of the skeletal mass as reliable assessments of sarcopenia in CD surgery in a cohort of 230 patients, however although all CD operations were included only major postoperative complications were reported, whilst our study reported on all postoperative outcomes in the specific group of patients with CD undergoing primary ileocaecal resection.…”
Section: Discussionmentioning
confidence: 99%
“…The association between preoperative muscle mass and postoperative outcome has been investigated in several different studies. A low value for muscle mass derived from preoperative imaging, for instance, is related to a significantly higher rate of major postoperative complications in patients with Crohn's disease [11] and of overall complications after colon resection [12]. Previous research showed that the decrease in fat mass is accompanied by a reduction of LBM [13,14].…”
Section: Discussionmentioning
confidence: 99%